Changing Roles of NGOs in the Creation, Storage and Dissemination of Information in Developing Countries - Witt, Steve W. (De Gruyter, 2006)
Non-governmental organizations (NGOs) are growing exponentially. In 1993, the Yearbook of International Organizations listed 16,000 internationally recognized NGOs. By 2004, this number was 63,000. With this increase comes a staggering growth in the activities and intellectual output of NGOs working on a local and international level. As the mission of both libraries and NGOs increasingly intersect, these organizations must collaborate to provide essential services that revolve around the creation, dissemination, and storage of information. This volume's eight essays focus on collaborative work between NGOs and libraries in the study and resolution of global issues ranging from AIDS to food security, and social transformation.
English
Keywords: Libraries